Influence of changing direction on the center of gravity and knee joint angle in rugby players - Sunagawa, N.; Fukubayashi, T. (Sports injuries and prevention, 2015)
While rugby is a collision sport, many anterior cruciate ligament (ACL) injuries of the knee involve noncontact changes of direction. This study investigates the risk factors of ACL injury in rugby players by establishing the relationship between noncontact directional change by the players and the consequent alteration of the player`s center of gravity (CG) and knee joint motion. Methods: Photographs were taken when players at a university rugby football club changed their direction of movement by 45° or 90° (n = 10). The player`s motions were assessed to determine 3- and 2-dimensional coordinate values of markers on the players by using the direct linear transformation method. The values were used to calculate knee joint flexion 40 ms after foot grounding, the CG position (height and rearward position), and the abduction angle of the knee joint. A paired t test was used for statistical analysis; a probability level of less than 5 % was considered significant. Results and Discussion: No significant differences were observed in the knee flexion angle between a 45° and a 90° change in direction. However, the CG position (height and rearward position) and the abduction angle of the knee joint increased as the magnitude of the change in direction increased (p < 0.01). Because increases in the rearward CG and abduction angle of the knee joint are considered risk factors for ACL injury, the risk of ACL injury is predicted to go up as the magnitude of the change in direction increases.